The influence of digital marketing on decision to use Premier League Mobile Online Game on Gen-Z - Muhammad Aqil Taqiyuddin; Terra Saptina Maulani (Marketing Management Studies, 2022)
This Study examines Digital Marketing channels (Website, Display Ads, Search Ads, E-Mail, and Social Media) in the online game Mobile Premier League. This study analyses the influence of Digital Marketing Channels on the Decision to Use the online game Mobile Premier League on Gen-Z in Bandung. The research method in this study is descriptive analysis and verification analysis, description analysis was calculated using the range interval method, and verification analysis was calculated using multiple linear regression test, correlation coefficient, and coefficient of determination. With data collection techniques through the distribution of questionnaires to 100 Gen-Z respondents in the city of Bandung who used the online game Mobile Premier League. These results showed that simultaneously Website, Search Ads, Display Ads, E-Mail, and Social Media have no significant effect on the decision to use with a coefficient of determination of 0,030 which means Digital Marketing (Website, Search Ads, Display Ads, E-Mail, and Social Media) affect the decision to use by 3% while the remaining 97% is influenced by other variables or factors not examined in this study.